Surface displacements on faults triggered by slow magma transfers between dyke injections in the 2005–2010 rifting episode at Dabbahu–Manda–Hararo rift (Afar, Ethiopia). Issue 1 (23rd November 2015) - Dumont, S.; Socquet, A.; Grandin, R.; Doubre, C.; Klinger, Y.
Abstract: The rifting episode that occurred in Dabbahu–Manda–Hararo (Ethiopia) between 2005 and 2010 during which 14 dyke intrusions were emitted, was a unique opportunity to study interactions between tectonic deformation and magmatic processes. While magmatism has been shown to control primarily the spatial and temporal distribution of dyke intrusions during this accretion sequence, the role of faults in accommodating plate spreading in rift segments is poorly understood. During interdyking periods, transient ground deformation due to magma movement is generally observed. Investigating such a small-scale deformation and in particular the movement along faults during these periods will help understanding the factors that trigger fault movement in magmatic rifts. We analyse fault activity during three interdyking periods: 2006 December–June (d0–d1), 2007 January–July (d5–d6) and 2009 November–January (d10–d11). The time–space evolution of surface displacements along ∼700 faults is derived from pairs of ascending and descending SAR interferograms. Surface slip distributions are then compared with codyking ground deformation fields. The results show that faults are mainly activated above the areas affected by magma emplacement during interdyking periods. A detailed analysis of brittle deformation during the six months following the 2005 September intrusion shows asymmetric deformation on the rift shoulders, with significant opening on faults located to the west of the dyke. We explain this feature by the activation of westward dipping pre-existing faults, with block rotations in between. In addition, we observe that the strip encompassing the activated faults narrows by 30 per cent from co- to interdyking period. This suggests that magma keeps migrating to shallower depths after the dyke intrusion. During a rifting episode, activation of faults in a pre-existing fracture network therefore seems to be mainly controlled by deep magma processes.